The impact of shariah board on the performance of Islamic banks and the relevance of shariah committee (BNM) new ruling on the restructuring of Islamic financing facility during the pandemic crisis - Haron, Razali; Radzali, Nur Ermiedza; Nomran, Naji (İLKE Science Culture Education Foundation, 2021)
This study examines the impact of Shariah Board (SB) characteristics on the financial and social performance of Islamic banks (IBs) from the perspectives of Agency Theory (AT), Stewardship Theory (ST) and the Resource Dependence Theory (RDT). To meet its objective, GMM is employed on a panel data of 15 IBs in Malaysia from 2010 to 2018 covering the pre and post implementation of IFSA 2013 with three performance measurements; ROA and ROE (financial performance) and Zakat over Asset (social performance). SB education, SB reputation, and SB expertise are positively related to IBs performance; while SB remuneration and SB cross membership are negatively related to performance. SB size is found to be insignificant. The study therefore concludes SB is relevant to the performance of IBs. The study also discusses the response of SB at the central bank (SAC-BNM) via its new ruling on financing restructuring in alleviating the hardship of IBs’ customers during the pandemic crisis.